Analisis Learning Obstacle Siswa Kelas X SMA Negeri 1 Batu Ampar Dalam Memecahkan Masalah Statistika - Lusita Dewi; Syarifah Fadillah Al Hadad; Sandie Sandie (LPD Universitas PGRI Pontianak, 2026)
This research aims to describe the learning obstacles experienced by tenth-grade students of SMA Negeri 1 Batu Ampar in solving problems related to statistical material. This study employs a qualitative approach within the form of a case study. The research subjects were selected using purposive sampling, consisting of six students categorized by high, medium, and low ability levels. The data were collected through diagnostic tests, interviews, and documentation, and then analyzed through several stages, including data processing, data classification, data analysis, and drawing conclusions. The validity of the data was tested using source triangulation. The findings indicate that students still experience difficulties in understanding statistical concepts, particularly in determining the mean, median, and mode, selecting appropriate problem-solving steps, and interpreting data. These learning obstacles manifest in the form of calculation errors, procedural mistakes, and the inability to apply concepts to different problem contexts. Furthermore, the results show that students’ learning challenges are influenced by several factors, including: (1) Internal factors, such as low conceptual understanding, lack of mastery of prerequisite material, low learning motivation, and the tendency to memorize formulas without understanding their meaning; (2) External factors, including instructional methods that remain procedural and provide limited gradual practice; and (3) Learning material factors, particularly limited variations of example problems and lack of contextual presentation. These findings indicate that the learning process still requires reinforcement in conceptual understanding, diverse practice exercises, and more contextual learning strategies in order to minimize learning obstacles among students.Keywords: Diagnostic test, Learning Obstacle, Material understanding, Statistic.